Dampak komunikasi interpersonal terhadapminat dan kepuasaan siswa saat pembelajaran online di SMA Pesat - Islamiah, Siti Suhaesul (Komunika: Journal of Communication Science and Islamic Dakwah, 2022)
Abstract Thisxstudyxdiscussesxthexrelationshipxof interpersonal communication on student interest and satisfaction. The purpose of this study is to determine the impact of interpersonal communication on student interest and satisfaction. In this study, the researchers used quantitative research with a field research approach, the technique for obtaining the sample was random sampling, and the results were 108 respondents. The results of the normality test with the one-sample kolmogorov-Smirnovxget Asymp.results Sig.(2-tailed)x=x0.200x<x0.05, it can be stated that interpersonal communication on student interest and satisfaction is normally distributed. The homogeneity test got the results (P – Value) for interest in learning = 0.276 and (P – Value) student satisfaction = 0.052, then 0.276 > 0.05 and 0.052 > 0.05 can be stated the data distribution is the same (homogeneous). The results of the hypothesis test to get the results of rcount= 0.801 for interpersonal communication relationships to interest in learning and rcount = 0.849 for interpersonal communication on student satisfaction with rtable = 0.195 then it is found that rcount > rtable, namely 0.801 > 0.195 and 0.849 > 0.195. So it can be concluded that the impact of interpersonal communication on student interest and satisfaction in the online learning process is said to be positive. In the future, teachers will continue to improve their self-competence and create a more pleasant learning atmosphere and students will find comfort in learning. Abstrak Penelitian ini membahas tentang hubungan komunikasi interpersonal terhadap minat dan kepuasaan siswa. Tujuan penelitian ini adalah untuk mengetahui dampak komunikasi interpersonal terhadap minat dan kepuasaan siswa. Dalamxpenelitianxini, peneliti menggunakanxjenisxpenelitian kuantitatifxdenganxpendekatan Field Research, teknik untuk mendapatkan sampel peneliti menggunakan samplingxrandom, danxmendapatkan hasil 108 responden. Hasil dari uji normalitas dengan one-sample kolmogorov-Smirnov mendapatkan hasil Asymp. Sig. (2-tailed) = 0.200 < 0,05 maka dapat dinyatakan bahwa komunikasi interpersonal terhadap minat dan kepuasaan siswa berdistribusi normal. Uji homogenitas mendapatkan hasil (P – Value) untuk minat belajar = 0.276 dan (P – Value) kepuasaan siswa = 0.052, maka 0.276 > 0.05 dan 0.052 > 0.05 dapat dinyatakan distribusi data sama (homogen). Dari hasil uji hipotesis mendapatkan hasil = 0.801 untuk hubungan komunikasi interpersonal terhadap minat belajar dan = 0.849 untuk komuninkasi interpersonal terhadap kepuasaan siswa dengan = 0.195 maka didapati > yaitu 0.801 > 0.195 dan 0.849 > 0.195. Maka dapat disimpulkan dampak komunikasi interpersonal terhadap minat dan kepuasaan siswa dalam proses pembelajaran online dikatakan positif. Kedepannya guru terus meningkatkan kompetensi diri dan menciptakan suasana pembelajaran yang lebih menyenangkan dan siswa mendapatkan kenyamanan untuk belajar.